PENGARUH MODAL INTELEKTUAL, KEPEMIMPINAN DAN KOLABORASI MITRA BISNIS TERHADAP INOVASI DAN KEUNGGULAN BERSAING (Studi Pada Industri Logam dan Mesin di Kabupaten Tegal) - Oktaviani, Karina Dwi; Rahardjo, Susilo Toto (Diponegoro Journal of Management, 2017)
The purpose of this research is to determine factors that can affects innovation on competitive advantage in the small and medium industries of metals and machinery were still able to survive in the current competitive environment. Intellectual capital, leadership, and business partner collaboration are all factors used in this study that may affect innovation.      The population in this study is small and medium-scale industries in the metal processing sector in Tegal regency, while the sample was taken of 120 companies / metalworkers. Model analysis using two steps linear regression analysis using SPSS 21.      The results showed that: 1) intellectual capital and leadership is a factor that can affect the appearance of innovation, while business partner collaboration doesn’t indicate influence on innovation, with coefficient regression ; 2) innovation has a very strong influence on the competitive advantages, with coefficient regression .